Pendekatan Psikologi Pendidikan Islam dalam Mengatasi Problematika Belajar Siswa - Wauran, Meissara Putri Andannari; Rolhimah, Siti (Lembaga Yasin AlSys, 2026)
Students’ learning problems are a complex phenomenon encompassing cognitive, affective, and spiritual dimensions, whereas conventional educational psychology approaches tend to emphasize cognitive and behavioral aspects, resulting in suboptimal integration of value-based and spiritual dimensions. This article aims to analyze the role of the Islamic Educational Psychology approach in addressing students’ learning problems through the integration of psychological, pedagogical, and Islamic value dimensions. The study employed a qualitative method with a systematic literature review approach of primary sources, including reputable journal articles, academic books, and scholarly works relevant to Islamic Educational Psychology. Data analysis techniques involved data reduction, thematic categorization, and conceptual synthesis. The findings indicate that the Islamic Educational Psychology approach can provide comprehensive solutions to students’ learning problems by strengthening intrinsic motivation, developing spiritual intelligence, cultivating moral character, and fostering humanistic educational relationships between educators and students. The study concludes that the Islamic Educational Psychology approach makes a significant contribution to creating a holistic and meaningful learning process, with implications for the importance of integrating Islamic Educational Psychology into instructional practices and educational policies to sustainably improve students’ learning quality.